2015
DOI: 10.1155/2015/341759
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Origins of Quality Gaps in Discharge Summaries: A Survey of Resident Physician Attitudes

Abstract: Because little is known about attitudes of primary authors of discharge summaries in academic institutions, namely trainees and physician assistants (PAs), we sought to explore values, possible areas for improvement, and interest in formal discharge summary education. A survey composed of Likert scale analyses, dichotomous relationships, and open-ended questions was designed using focus groups and validated via expert committee review. Of 135 total residents (PGY 1-3), 79 residents and 10 PAs in a large academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The junior doctor education around appropriate documentation of investigations, such as the inclusion of relevant information that was appropriately summarized, was successful. This showed that continued education can produce sustained results [8,9], which is consistent with findings from our background research.…”
Section: Discussionsupporting
confidence: 91%
“…The junior doctor education around appropriate documentation of investigations, such as the inclusion of relevant information that was appropriately summarized, was successful. This showed that continued education can produce sustained results [8,9], which is consistent with findings from our background research.…”
Section: Discussionsupporting
confidence: 91%
“…Discharge summaries are an ideal starting place, as the literature provides several examples of how to teach and evaluate residents' discharge summaries. [24][25][26] Similar to other studies, 16,27 our results suggest that formal discharge summary review is underutilized, despite evidence of its efficacy. Conducting discharge summary reviews is an excellent starting point for programs seeking to build transitions of care curricula rooted in competency-based education.…”
Section: Figuresupporting
confidence: 86%
“…Previous studies have shown that junior clinicians feel that specific training in discharge documentation would be of benefit. 16 Therefore, there have been numerous previous attempts to carry out projects that aim to improve the quality of discharge summaries. 17,18 Techniques employed have ranged from the provision of one-off and regular teaching sessions to clinicians through to programmes providing both teaching and feedback.…”
Section: Discussionmentioning
confidence: 99%